Earthquake Swarms Triggered by Groundwater Extraction Near the Dead Sea Fault. Issue 14 (29th July 2019) - Wetzler, Nadav; Shalev, Eyal; Göbel, Thomas; Amelung, Falk; Kurzon, Ittai; Lyakhovsky, Vladimir; Brodsky, Emily E.
Abstract: In 2013 and 2018, earthquake swarms with a maximum moment magnitude of 4.5 occurred 5 km from the northern section of the Dead Sea Transform Fault. Here we show that aquifer pressure data, interferometric synthetic aperture radar surface deformation time series, and seismic monitoring suggest that groundwater withdrawal triggered these earthquakes. Continuous groundwater extraction from several wells located 10 km west of the swarms has accelerated since 2010 and resulted in a total decrease of 50 m of the groundwater level at the time of the 2018 earthquake swarm. The withdrawal also corresponds to surface subsidence of 10 mm/year based on repeat interferometric synthetic aperture radar measurements. The temporal correlation, extensive subsidence, anomalous swarm characteristics, and normal faulting orientation suggest a connection between the groundwater withdrawal and recent earthquakes. Poroelastic modeling demonstrates that pumping‐induced pore pressure decrease west of the earthquake could have caused significant dilatational stresses that led to normal faulting events outside the aquifer. Key Points: Two anomalously shallow earthquake swarms occurred below Lake Kinneret following periods of rapid groundwater extraction Water level decrease and extensive ground subsidence captured by InSAR are correlated with the earthquake swarms Poroelastic modeling supports earthquake triggering by groundwater extraction